EFEKTIVITAS STRATEGI PEMBELAJARAN SCAFFOLDING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Nuriavani, Dina; Rahmawati, Dwi; Agustina, Rina (Universitas Muhammadiyah Metro, 2024)
This aim of the research to determine the effectiveness of the scaffolding learning strategy on mathematical problem solving abilities at UPTD SMPN 1 Sekampung Udik. The research method used is quantitative with a quasi-experimental type. The sampling technique used cluster sampling involving 7 classes so that class VIII C was obtained as an experimental class using scaffolding learning with a number of students, namely 30 and class VIII D as a control class using expository learning with a number of students, namely 29. This research instrument used ability test questions. mathematical problem solving, observation sheets, and interview guide sheets, as well as all instruments have been validated. Data collection techniques use tests, observations, and interviews as well as using data analysis techniques in the form of normality tests, homogeneity tests, and t-tests. Based on the results of research and hypothesis testing using the t-test, the results showed that tcount = 3.02 > ttable = 2.00247, meaning that the mathematical problem solving abilities of those who received scaffolding learning were higher than those who received expository learning. Thus it is concluded that the scaffolding learning strategy is effective on mathematical problem solving abilities at UPTD SMPN 1 Sekampung Udik.